HAK ANAK TERHADAP MANTAN ANGGOTA ISLAMIC STATE OF IRAQ AND SYRIA - Salsabilla, Rizma; Ahmad, Muh. Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This research describes a case regarding the rights of children of a former body of the Islamic State of Iraq and Syria (ISIS) after the authorities handled the cancellation of the citizenship status of former ISIS conscripts without any trial. This research intends to identify legal provisions, especially regarding nationality. In a special way, this thesis understands the national status of women and children of former ISIS military conscripts. This research method uses a juridical normative approach with a legal approach (statute approach) and a problem approach (case approach). The results of the research ensure that the national status of former ISIS conscripts cannot disappear by itself if it does not comply with the provisions of Article 31 of the Regulation of the Ruler of the Republic of Indonesia No. 2 of 2007 concerning Rules for Obtaining, Expending, Canceling, and Retrieving the Nationality of the Republic of Indonesia. A person’s national status is an elementary right and precious right. The national principles contained in Law Number 12 of 2006 concerning nationality also guarantee and prevent a person from having his citizenship status so that it cannot be revoked just like that without a trial